Immunological Identification of Three Urokinases - Day, Eugene D.; Ball, Anne P. (Thrombosis and Haemostasis, 1970)
A third urokinase has been detected by immunochemical tests in two clinical preparations of urokinase, one from Abbott and one from Sterling-Winthrop. It is component V in a series of components found in Sterling-Winthrop clinical urokinase. Components I and II are confined to Sterling-Winthrop urokinase whereas components III, IV, and V are present also in Abbott urokinase. Evidence suggests but does not prove that V is the SI component of Abbott; that IV is the S2 component of Abbott as well as the crystalline component of Sterling -Winthrop ; and that III is a higher molecular weight species of urokinase, unrelated to either IV or V, which may correspond to the 104,000 MW uroprotein of Doleschel and Auerswald. It is proposed that III be referred to as S3.